VEGFA variants are associated with pre‐school lung function, but not neonatal lung function. Issue 11 (24th October 2013) - Kreiner‐Møller, E.; Chawes, B. L. K.; Vissing, N. H.; Koppelman, G. H.; Postma, D. S.; Madsen, J. S.; Olsen, D. A.; Baty, F.; Vonk, J. M.; Kerkhof, M.; Sleiman, P.; Hakonarsson, H.; et al.
Summary: Background: Vascular endothelial growth factor (VEGF) is implicated in airway remodelling and asthma development. We studied VEGFA gene variants and plasma levels and the development of lung function, bronchial hyperresponsiveness and asthma in childhood. Methods: We analysed 13 SNPs in the VEGFA gene in 411 children from the COPSAC2000 high‐risk birth cohort. Asthma was diagnosed prospectively, and lung function measurements were obtained at birth and 6 years of age. Plasma VEGF levels were measured at 18 months of age. We used a Bonferroni adjusted significance level. Findings were replicated in the Prevention and Incidence of Asthma and Mite Allergy (PIAMA) birth cohort at age 8. Results: At age six, three SNPs from the same linkage block were associated with FEV1 (rs699947, P  = 1.31E‐05), independent of asthma, and there were suggestive associations between FEV1/FVC ratio and rs833052 and maximal mid‐expiratory flow and rs6900017. Replication in the PIAMA cohort showed borderline association between FEV1 and rs699947 and significant meta‐analysis result. SNPs upstream and nearby rs699947 were nominally associated with VEGF plasma levels. VEGF levels were not associated with asthmatic symptoms or lung function measures. Conclusions and Clinical Relevance: VEGF gene variants are associated with lung function at school age, but not at birth, suggesting a role of VEGF in post‐natal lung function development.